Effects of Gradually Decreased Temperature on Pre- Adult Development, Adult Emergence, Sex Ratio and Weight of Pimpla turionellae (Hymenoptera: Ichneumonidae) - NURULLAHOĞLU, ZAHİDE ULYA (FOUNDATION ENVIRONMENTAL PROTECTION & RESEARCH-FEPR, 2012)
The effects of gradually decreased temperature on pre-adult development of endoparasitoid Pimpla turionellae (Hymenoptera: Ichneumonidae) reared on Galleria mellonella (Lepidoptera: Pyralidae) pupae at laboratory conditions were investigated. Parasitized host pupae were acclimated at a gradually decreased temperature; for 3 days at each 25, 20, 15 and 10 degrees C, and then kept in separate four groups for 2, 3, 4 and 5 days at 4 degrees C. Pre- adult development time, adult emergence, sex ratio and weight of wasps were determined for each treatment. Adult emergence of treatment groups lasted longer than controls for both sex and that time was observed to increase approximately 50% in the adult from experimental group which was kept for 5 days at 4 degrees C. Adult emergence ratio also decreased by increasing acclimation time at 4 degrees C. While ratio of adult emergence of female was equal with that of male in the control group, that of female was found to be more than that of adult male by increasing acclimation time at 4 degrees C. The weight of females decreased while there was no difference in that of males. However, the data showed that any difference wasn't statically determined between the weigh of the control and experimental groups.
Keywords: Decreased temperature; hymenoptera; Pimpla turionellae; pre-adult development; ratio of adult emergence; weight of adult; INSECT COLD-HARDINESS; BRACONIDAE; SURVIVAL; SUCCESS; CULTURE